A PROCESS FOR ASSESSING ORGANIZATION - Djordjevic, Branislav (Journal of process management and new technologies, 2021)
The process of conducting an evaluation of organization design and performance remains a form of art or craft which each researcher or analyst is forced to learn by apprenticeship or reinvent by trial and error. Most research methodology texts assume that the researcher is the sole decision maker and user of the results of a studying question. In practice, assessments of complex organizations occur in contexts where the interests and value judgments of many stakeholders need to be taken into account. As a result, people who are commissioned to conduct an organization assessment are confronted with three problems that are largely ignored by organization theorists and research methodologists. (1) Who should decide what measures should be used as the criteria for evaluating an organization? (2) Whose conceptual model or framework should be used to guide the assessment? (3) How can facilitate learning and use of results within the organization being assessed?                This chapter delves into these problems by attempting to (1) clarify some of the conceptual confusion on goals, values, and facts regarding measures of organizational effectiveness. (2) suggest a process model that may be useful for designing and  conducting studies to assess organization design and performance, and (3) report our learning experiences in using the process model to guide two longitudinal assessments of organizations.